The Influence of Tax Knowledge, Taxpayer Awareness and Trust in the Tax Authority on Taxpayer Compliance in Paying Rural and Urban Land and Building Taxes in Pusomaen District, Southeast Minahasa Regency - Ananda Pananginan; Jullie J. Sondakh; Robert Lambey (Formosa Journal of Applied Sciences, 2023)
This research aims to determine whether tax knowledge, taxpayer awareness and trust in the tax authorities have a positive and significant effect on taxpayer compliance in paying rural and urban land and building taxes (PBB-P2) in Pusomaen District, Southeast Minahasa Regency. The research method used in this research is a quantitative method. The number of samples used was 97 respondents using a sample collection method, namely probability sampling, using a simple random sample technique collected through a questionnaire (google form). The analytical method used is multiple linear regression analysis with the help of the SPSS application. The results of this research show that tax knowledge, taxpayer awareness and trust in the tax authorities have a positive and significant effect on taxpayer compliance in paying land and building taxes in Pusomaen District, Southeast Minahasa Regency.